Economic growth, education and AIDS in Kenya: a long-run analysis - Bell, Clive (Policy research working paper, 2006)
The AIDS epidemic threatens Kenya with a long wave of premature adult mortality, and thus with an enduring setback to the formation of human capital and economic growth. To investigate this possibility, the authors develop a model with three overlapping generations, calibrate it to the demographic and economic series from 1950 until 1990, and then perform simulations for the period ending in 2050 under alternative assumptions about demographic developments, including the counterfactual in which there is no epidemic. Although AIDS does not bring about a catastrophic economic collapse, it does cause large economic costs-and many deaths. Programs that subsidize post-primary education and combat the epidemic are both socially profitable-the latter strikingly so, due to its indirect effects on the expected returns to education-and a combination of the two interventions profits from a modest long-run synergy effect
Gesehen am 14.05.2021
Keywords: 1950-2050